Autômatos celulares e sistemas bio-inspirados aplicados ao controle inteligente de robôs - Lima, Danielli Araújo (2017)
In several situations, the volume of tasks to be accomplished can not be performed by a single robot. Thus, a field that has attracted growing interest is the behavior investigation of the search swarm robots. Cooperation and control strategies of this swarm should be considered for an efficient performance of the robot team. There are several classic techniques in artificial intelligence that are able to solve this problem. In this work a set of bio-inspired techniques, which includes a model based on cellular automata with memory and inverted pheromone, was initially considered to coordinate a team of robots in the task of foraging to previously known environments. The team's robots share the same environment, communicating through the inverted pheromone, which is deposited by all agents at each step of time, resulting in repulsive forces and increasing environmental coverage. On the other hand, the return process to the nest is based on the social behavior observed in the process of pedestrian evacuation, resulting in forces of attraction. All movements in this process are first choice and conflict resolution provides a non-deterministic characteristic to the model. Subsequently, the base model was adapted for the application in the tasks of selective collection and search and rescue. The results of the simulations were presented under different environment conditions. In addition, parameters such as amount and arrangement of food, nest position and width, pheromone-related constants, and memory size were analyzed in the experiments. Then, the base model proposed in this work for foraging task, was implemented using the e-Puck robots in the simulation environment Webots, with the appropriate adaptations. Finally, a theoretical analysis of the investigated model was analyzed through the graphs and queuing theory. The method proposed in this work proved to be efficient and capable of being implemented at a high level of parallelism and distribution. Thus, the model becomes interesting for the application in other robotic tasks, especially in problems that involve parallel multi-objective search.